Effect of anexiolytic dose of medazolam on Incidence of intraoperative nausea and vomiting during spinal cesarean section - Myasar Jasim Mohammed; Kadhum Jody Rokan (International Journal of Health and Medicine, 2024)
Opioids have sedative properties and can lessen intraoperative nausea and vomiting (IONV), even if they may cause nausea and vomiting. The current work was aimed to evaluate the effect of anxiolytic dose of midazolam on Incidence of intraoperative nausea and vomiting during spinal cesarean section. The study was conducted from October 2023 to April 2024 with approval from the research and ethics committees of the university. once an informed consent form has been signed, full-term (90) pregnant participants were included, and scheduled for cesarean section (CS) under spinal anesthesia at Al-Shifa Private Hospital in Baqubah, Diyala. Data from all participants were analyzed. demographic data was non-significant (P≤0.05) variance in the experimental group compared with the control group. The mean blood pressure in both groups, as it was measured every 10 minutes, starting from 0 to 40 minutes of the operation, and there were no significant (P≤0.05) variance between the two groups. The findings showed that the 27 (60%) cases of Nausea and vomiting in the control group, which revealed a significant (P≤0.05) variance compared with the medazolam group, if the number of cases was 8 (17.8%). We conclude that the incidence of intraoperative nausea and vomiting during cesarean sections performed under spinal anesthesia is significantly influenced by the dosage of anxiolytic drugs.